2014
DOI: 10.1038/srep04726
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Atomic Layer-by-Layer Oxygen Vacancy-Exchange Diffusion in Double-Perovskite LnBaCo2O5.5+δ Thin Films

Abstract: Surface exchange and oxygen vacancy diffusion dynamics were studied in double-perovskites LnBaCo2O5.5+δ (LnBCO) single-crystalline thin films (Ln = Er, Pr; −0.5 < δ < 0.5) by carefully monitoring the resistance changes under a switching flow of oxidizing gas (O2) and reducing gas (H2) in the temperature range of 250 ~ 800°C. A giant resistance change ΔR by three to four orders of magnitude in less than 0.1 s was found with a fast oscillation behavior in the resistance change rates in the ΔR vs. t plots, sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
28
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 27 publications
3
28
1
2
Order By: Relevance
“…However, there are very few reports on the gas-sensing materials using p -type oxide semiconductor, such as NiO373839, CuO40, LaFeO 3 41, Co 3 O 4 ,4243444546474849505152535455 LBCO1623. Compared with n-type oxide semiconductor for gas-sensing, the p-type oxide semiconductors with distinctive surface reactivity and oxygen adsorption can enhance gas selectivity, decrease the dependence of humidity to negligible level and improve the recovery speed, reviewed by Kim and Lee46.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are very few reports on the gas-sensing materials using p -type oxide semiconductor, such as NiO373839, CuO40, LaFeO 3 41, Co 3 O 4 ,4243444546474849505152535455 LBCO1623. Compared with n-type oxide semiconductor for gas-sensing, the p-type oxide semiconductors with distinctive surface reactivity and oxygen adsorption can enhance gas selectivity, decrease the dependence of humidity to negligible level and improve the recovery speed, reviewed by Kim and Lee46.…”
mentioning
confidence: 99%
“…When LBCO thin film is exposed to the reducing gas, parts of Co +4 changed into Co +3 and the resistance increases. In the contrast, the gas change to oxidizing gas, parts of Co +3 changed into Co +4 and the resistance decreases5152. Ethanol vapor is safer and more active than other gas, such as H 2 , ammonia, hydrogen sulfide, which is used as the representative of reducing gases.…”
mentioning
confidence: 99%
“…На дефектность приповерхностных слоев нанострук-турированного GdBaCo 2 GdBaCo 2 O 5.55 и GdBaCo 2 O 5.1 -крупнозернистые об-разцы, полученные по стандартной керамической тех-нологии при различных давлениях кислорода. Спек-тральная область от 528 до 532 eV (особенности a и b) образована смешиванием незанятых Co 3d(t 2g )-и Co 3d(e g )-состояний с O 2p-состояниями.…”
Section: результаты и их обсуждениеunclassified
“…Изучение природы наносостояния в двойных слоистых оксидах кобальта в основном сосредо-точено на проведении исследований пленок соответству-ющего состава [1,2]. В меньшей степени представлены исследования разупорядочения в системах LnBaCo 2 O 5+δ методами нагружения образцов высоким давлением [3].…”
Section: Introductionunclassified
“…In particular, LaBaCo 2 O 5.5+δ (LBCO) exhibits exotic electronic and magnetic properties from the intricate coupling of charge, spin, orbital, and lattice degrees of freedoms8910. It has been reported that different the oxygen content in LBCO can lead to CoO 5 pyramidal, CoO 6 octahedral or mixed structure, and it can significantly influence its electric transport properties1112. If there are the mixture of Co 3+ /Co 4+ in the film, the film will shows the semiconductor or metallic behavior dependent on the test temperature range due to double exchange mechanism.…”
mentioning
confidence: 99%